ACUTE INTESTINAL INFECTION AS A DISGUISE OF ACUTE APPENDICITIS IN CHILDREN - Y. Y. Dyakonova; I. V. Poddubniy; L. S. Namazova-Baranova; M. D. Bakradze; A. A. Gusev; A. S. Bekin (Union of pediatricians of Russia, 2016)
The issue of differential diagnosis of acute appendicitis and acute intestinal infections in contemporary medicine remains relevant for clinical practice of surgeons and pediatricians. Late diagnosis of appendicitis results in development of complicated forms of vermiform appendix inflammation. This prolongs operative intervention, duration of antibacterial therapy and duration of a child's inpatient stay. The article presents clinical observation of three children treated for perforated appendix and generalized purulent peritonitis. The described cases demonstrate the need in multidisciplinary approach and complex diagnosis of patients with such complaints as abdominal pain, fever and diarrhea.